Evaluation of the Depression Status of Nurses Working in a State Hospital - Genç, Ezgi; Pirinçci, Edibe; Özbey, Sedap; Özdemir, Serap; Demir, Abdullah; Deveci, Süleyman; Oğuzöncül, Ayşe (Muğla Sıtkı Koçman Üniversitesi, 2022)
Depression is a serious illness associated with memory, cognitive functions, mood disorders and physical and behavioral changes. This descriptive study was conducted to determine depression status and related factors in nurses. This research was applied to all nurses working at Tunceli State Hospital. The research data were collected using the Personal Identification Form, which were prepared by the researchers, and Beck Depression Inventory (BDI). T test, one-way ANOVA were used for statistical analysis of the data. The mean age of the nurses in the study was 34.15±8.94 and 88.4% were female. The mean BDI score of the nurses was 11.87±7.50 and 24.6% had depression. BDI scores age was higher in nurses with chronic illness, perception of socioeconomic status as poor, and smoking and alcohol use (p<0.05). BDI scores did not change according to gender, marital status, education level (p>0.05). Depression were found in approximately one quarter of nurses. Nurses are role models in society. Therefore, measures should be taken to conduct regular health checks of nurses, and to minimize stressors related to the work environment.

Depresyon; bellek, bilişsel işlevler, duygu durum bozulmalarına eşlik eden, fiziksel ve davranış değişikliklerinin ortaya çıktığı ciddi bir hastalıktır. Tanımlayıcı tipteki bu çalışma, hemşirelerde depresyon durumlarını ve ilişkili faktörleri belirlemek amacıyla yapılmıştır. Bu çalışma Tunceli Devlet Hastanesi’nde görev yapan tüm hemşirelere uygulanmıştır. Anket formunda “Kişisel Tanıtıcı Form” ve “Beck Depresyon Ölçeği (BDÖ)” kullanılmıştır. Verilerin istatistiksel analizlerinde t testi, tek yönlü varyans analizi kullanılmıştır. Hemşirelerin yaş ortalaması 34.15±8.94 olup, %88.4’ü kadındır. Hemşirelerin BDÖ puan ortalaması 11.87±7.50 olup, %24.6’sında depresyon saptanmıştır. BDÖ puanları; yaş arttıkça, kronik hastalığı olanlarda, sosyoekonomik düzeyini kötü algılayanlarda, sigara, alkol kullananlarda daha yüksektir (p<0.05). BDÖ puanları cinsiyete, medeni duruma, eğitim durumuna göre değişmemektedir (p>0.05). Hemşirelerin yaklaşık dörtte birinde depresyon saptanmıştır. Hemşireler toplumda rol model olan insanlardır. Bu yüzden düzenli sağlık kontrollerinin yapılması, iş ortamı ile alakalı stresörlerin en aza indirilmesi için önlemler alınmalıdır.
Bir Devlet Hastanesinde Görev Yapan Hemşirelerin Depresyon Durumlarının Değerlendirilmesi
Keywords: Clinical Sciences; Klinik Tıp Bilimleri